Pre-ECMO Coagulopathy does not Increase the Occurrence of Hemorrhage during Extracorporeal Support. Issue 5 (May 2017) - Anton-Martin, Pilar; Raman, Lakshmi; Thatte, Nikhil; Tweed, Jefferson; Modem, Vinai; Journeycake, Janna
Introduction and methods: Observational retrospective cohort study to evaluate the association between precannulation coagulopathy and the occurrence of hemorrhage during extracorporeal membrane oxygenation (ECMO) in neonatal and pediatric patients at a tertiary children's hospital. Results: Of 241 patients supported with ECMO between January 2009 and December 2014, 175 (72.6%) had precannulation coagulation laboratory data and were included in the study. Of the eligible patients, 84 (48%) were identified as coagulopathic and 91 (52%) were noncoagulopathic. In the coagulopathic group, sepsis (27.3%) was the most common diagnosis leading to ECMO. Over half of the patients in both groups (55.9% of the coagulopathic and 52.7% of the noncoagulopathic group) developed hemorrhagic complications during ECMO support. The most frequent bleeding sites for both groups were the cannulation site (24%), the chest tube site (17%), and intracranial (10%). Pre-ECMO coagulopathy was not associated with higher incidence of hemorrhage during extracorporeal support (p = 0.76). Conclusions: Pre-ECMO coagulopathy was frequent in our cohort but did not increase the occurrence of hemorrhage during extracorporeal support. Although the identification of factors associated with hemorrhage is key to safely managing ECMO anticoagulation, the implication of precannulation coagulopathy seems to be minimal.